Autoconhecimento e alguns princípios do budismo, confucionismo e daoísmo nas artes marciais chinesas - de Oliveira Santos , Gilbert (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
Chinese martial arts have a diverse range of principles that underpin their practice. It is likely that no other martial art present, so powerfully, transiting aspects in different dimensions of knowledge, through art, medicine, thought, spirituality and self-knowledge. In this work, we will make a presentation about the self-knowledge and some principles of Chinese thought present in this technique. These principles enable dealing with the challenge of martiality of exciting and challenging way which the destructive character present in the martial gesture toward his subjective and philosophical dimension. This shift, when recognized in the practice of gesture, potentiates the reflection of his own existence and the conscious driving in everyday actions.